Description Of Mom Knowledge About Balanced Nutrition In Children Aged 24-36 Months In Preventing Stunting In Puskesmas Balai Jaya, Bagan Sinembah District In 2022 - Magda Siringo-ringo; Putri Agustina Hutabarat (Institute of Computer Science (IOCS), 2022)
Role mother in health 24-36 months old in gift nutrition to the development and growth of children demands mother must understand and knowing will needs nutrition . With the principle of balanced nutrition in children, namely by consuming food variety , get used to behavior life clean , do activity physical , maintain and monitor b tight b and (BB) normal . Stunting is problem not enough nutrition chronic , where if malnutrition occurs in children 24-36 months it will cause low access to nutritious food. This study aims to find out how the description of mother's knowledge about balanced nutrition in children aged 2 4 -3 6 months in preventing stunting at Balai Jaya Health Center in 2022. The method used in this research is descriptive method, with a total sampling technique of 35 respondents. From a total of 35 respondents, knowledge of